Intervention strategies in foreign exchange market - Vesna Martin (Economic Themes, 2020)
The goal of the paper is to present the intervention strategies used by central banks in order to influence the value of the domestic currency, transparency versus discretion when it comes to publishing data about FX intervention and the cost and effectiveness of intervention. It is rarely that nowadays countries allow for an exchange rate to be formed on the market basis through the effects of supply and demand for foreign exchange on the foreign exchange market. The central bank buys or sells a foreign currency in the foreign exchange market in order to increase or decrease the value of its national currency in comparison to the foreign currency. The reasons for the intervention are the reduction of short-term oscillations of the exchange rate, the impact at the level of foreign exchange reserves, as well as the maintaining the price and financial stability as the ultimate goal of most central banks. The paper will present intervention strategies on foreign exchange market, which involves the implementation of interventions in the market of options, forward, foreign currency repo and foreign currency swaps. Then, on the spot market, interventions using an auction, as well as the application of foreign currency indexed certificates.
Keywords: D53; E58; F31; G15; 330; FX intervention; FX market; swaps; forward; option